Rehabilitation of the alveolar bone after tooth extraction. Analysis of methods - Yu. A. Bakaev; I. A. Voronov; Yu. A. Generalova; Ya. A. Negorelova; M. E. Balashova; A. S. Karnaeva; V. M. Slonova (LLC "Endo Press", 2020)
Resorption of the alveolar bone after tooth extraction is an irreversible process due to biological bone remodeling. It will greatly complicate the further treatment of patients for dental implantation, since for the latter a prerequisite is a sufficient volume of bone tissue. It leads to a protracted treatment process: the volume and timing of interventions increases. The literature review has shown possible methods of preservation of the alveolar ridge after tooth extraction and the results of their application.